(untitled) (Medical Forum Monthly, 2024)
Objective: The aim of this study was focused on the distribution, determinants and dynamics of chronic hepatitis B in a specified population of Mansehra district. The application of this study is to control the health problem. Design of study: Original prospective observational study. Methodology: The prospective study was carried out in Shahina Jamil teaching hospital Abbottabad. Time period: 1st Jaunary 2005 to 1st june2008. All chronic patient (disease lasting for more than three months) were screened for hepatitis B. Redox kit (made in china) was used. Total three hundred people were screened belonging to Mansehra only. Results: It showed that chronic hepatitis B is fairly common (35%) in Mansehra with the age group of 15-70 year. More common in male and Male to female ratio is 3:1. It was also found that the disease is more common in low socioeconomic group and in labors mostly stayed away from family for a long time. Conclusion: Our study found that the hepatitis B is more common in Mansehra with incidence of 3.5% in NWFP. The rate is high in male. The knowledge of people about hepatitis B is inadequate. Hence a mandatory vaccination and health education is recommended.